Motor Cortex Excitability and BDNF Levels in Chronic Musculoskeletal Pain According to Structural Pathology - Caumo, Wolnei; Deitos, Alícia; Carvalho, Sandra; Leite, Jorge; Carvalho, Fabiana; Dussán-Sarria, Jairo Alberto; Lopes Tarragó, Maria da Graça; Souza, Andressa; Torres, Iraci Lucena da Silva; Fregni, Felipe (Frontiers in Human Neuroscience, 2016)
The central sensitization syndrome (CSS) encompasses disorders with overlapping symptoms in a structural pathology spectrum ranging from persistent nociception [e.g., osteoarthritis (OA)] to an absence of tissue injuries such as the one presented in fibromyalgia (FM) and myofascial pain syndrome (MPS). First, we hypothesized that these syndromes present differences in their cortical excitability parameters assessed by TMS, namely motor evoked potential (MEP), cortical silent period (CSP), short intracortical inhibition (SICI) and short intracortical facilitation (SICF). Second, considering that the presence of tissue injury could be detected by serum neurotrophins, we hypothesized that the spectrum of structural pathology (i.e., from persistent nociception like in OA, to the absence of tissue injury like in FM and MPS), could be detected by differential efficiency of their descending pain inhibitory system, as assessed by the conditioned pain modulation (CPM) paradigm. Third, we explored whether BDNF had an influence on the relationship between motor cortex excitability and structural pathology. This cross-sectional study pooled baseline data from three randomized clinical trials. We included females (n=114), aged 19 to 65 years old with disability by chronic pain syndromes: FM (n= 19), MPS (n=54), OA (n=27) and healthy subjects (n=14). We assessed the serum BDNF, the motor cortex excitability by parameters the TMS measures and the change on Numerical Pain Scale [NPS (0-10)] during CPM-task. The adjusted mean (SD) on the SICI observed in the absence of tissue injury was 56.36% lower than with persistent nociceptive input [0.31(0.18) vs. 0.55 (0.32)], respectively. The BDNF was inversely correlated with the SICI and with the change on NPS (0-10) during CPM-task. These findings suggest greater disinhibition in the motor cortex and the descending pain inhibitory system in FM and MPS than in OA and healthy subjects. Likewise, the inter-hemispheric disinhibition as well the dysfunction in the descending pain modulatory system is higher in chronic pain without tissue injury compared to a structural lesion. In addition, they highlight that a greater level of serum BDNF mediated the disinhibition of motor cortex excitability, as well the function of descending inhibitory pain modulation system, independently of the physiopathology mechanism of musculoskeletal pain syndromes.